"The thief of Bagdad" : an Arabian Nights fantasy - Walsh, Raoul, 1887-1980; Fairbanks, Douglas, 1883-1939; Douglas Fairbanks Pictures; Cinetel Films ([Los Angeles, CA] : Douglas Fairbanks Pictures, 1924)
A thief falls in love with the Caliph of Bagdad's daughter. The Caliph will give her hand to the suitor that brings back the rarest treasure after seven moons. --
Originally released as a motion picture in 1924.
Douglas Fairbanks, Snitz Edwards, Charles Belcher, Julianne Johnston, Sojin.
Cinematographer, Arthur Edeson; editor, William Nolan; music, Mortimer Wilson.
Silent, with English intertitles and musical accompaniment; Spanish subtitles.
Winner of the Kinema Junpo Award, 1926: Best Entertaining Film
Winner of the National Film Registry Award, 1996
Keywords: Thieves -- Arabian Peninsula -- Drama; Princesses -- Arabian Peninsula -- Drama; Rogues and vagabonds -- Drama; Baghdad (Iraq) -- Drama; Arabian nights -- Film adaptations; Silent films; Fantasy films; Film adaptations; Feature films; Internet videos; Streaming video